Analisis Risiko Investasi Saham pada Perusahaan Penyedia Jasa Layanan Internet Tahun 2015-2022 - Ramadhani, Aqsal Rizky; Yuliana, Lia (Politeknik Statistika STIS, 2023)
Every stock investor has an investment objective to gain profits. However, many investors still lack an understanding of the risks and benefits of their investments. Investors need to choose the right companies to invest in. The telecommunications sector is considered promising for investment, given the positive sentiments towards it since 2015. Nonetheless, companies within this sector vary in size, leading to differing investment risks.This research aims to analyze the investment risk level of companies with different sizes in the telecommunications sector. The analysis results indicate that large companies like TLKM, ISAT, and EXCL have lower stock price fluctuations compared to smaller companies like FREN, KBLV, and GOLD. This trend is also consistent with the movement of returns for these companies. Based on the Value at Risk (VaR) and average volatility, the lowest investment risk level is found in TLKM, while GOLD and KBLV have the highest investment risk.